2014
DOI: 10.5415/apallergy.2014.4.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Precise Climate Controller on the reduction of indoor microorganisms

Abstract: BackgroundNowadays, there are many methods to reduce microorganisms in the air, such as dehumidifier, air purifier or humidity and temperature controller. The Precise Climate Controller is an instrument for controlling humidity and temperature, a concept that is demonstrated.ObjectiveTo determine the efficacy of this device, in order to reduce the quantity of the fungi and bacteria in the closed system.MethodsThis study is a perspective experimental study and is conducted as follows - the air sample in the clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In a hospital room maintained at constant temperature and RH (25°C and 55%, respectively), fungal and bacterial cells were identified from air samples for at least 3 days; however, by day 6, no fungal or bacterial colonies were obtained from the air samples (Moungthong et al, 2014 ). Although these studies cannot confirm whether a certain room temperature and RH suppress the growth of indoor bacteria, they do suggest that both factors control microbial communities.…”
Section: Measured Factors At the Time Of Airborne Bacterial Sampling mentioning
confidence: 99%
“…In a hospital room maintained at constant temperature and RH (25°C and 55%, respectively), fungal and bacterial cells were identified from air samples for at least 3 days; however, by day 6, no fungal or bacterial colonies were obtained from the air samples (Moungthong et al, 2014 ). Although these studies cannot confirm whether a certain room temperature and RH suppress the growth of indoor bacteria, they do suggest that both factors control microbial communities.…”
Section: Measured Factors At the Time Of Airborne Bacterial Sampling mentioning
confidence: 99%
“…It has been known for quite a long time [ANSI/ASHRAE, 2012] that, in spaces with air speed less than 0.2 m/s, the RH within the range of 40 < RH < 60 and the temperature within the range of 22-27 • C together provide a comfort zone for humans and, meanwhile, this condition can eliminate pathogens (e.g. viruses, bacteria, funguses) and allergic substances as well as reducing or even eradicating house dust mites [Arlian et al, 2001;Moungthong et al, 2014;Sookchaiya et al, 2010].…”
Section: Engineering Design For Indoor Climate Controlmentioning
confidence: 99%
“…Next, to design and implement a real indoor climate control system, two benchmark models are reviewed to reveal some basic ideas. In [Moungthong et al, 2014] the room is closed for 20 days. The climate control results demonstrated that, for the first three days, there are nine A. flavus colonies found in the room.…”
Section: Engineering Design For Indoor Climate Controlmentioning
confidence: 99%
“…On the basis of recent research, the influence of individual environmental factors on airborne bacteria is becoming increasingly evident. For example, in a hospital room maintained at constant temperature and humidity (25°C and 55%), similar types of fungi and bacteria were identified over at least 3 days from air samples [ 16 ]. Furthermore, the study of airborne bacteria in patient rooms showed that the diversity and composition of the indoor bacterial communities changed readily in response to variations in ventilation or temperature [ 17 ].…”
Section: Introductionmentioning
confidence: 99%